NOVASI USAHA PENYEWAAN EVENT ORANIZER “NEW AFGAN NADA” DI DESA PANTENAN KECAMATAN PANCENG KABUPATEN GRESIK - Alfan Ahsanul Kulub (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research aims to find out the innovations made by the event organizer Afgan Nada. organizer Afgan Nada and find out the factors supporting and inhibiting factors in making innovations by renting event organizer services organizer Afgan Nada. Form The form of research used is qualitative research. Penelitian conducted in Desa Pantenan Kecamatan Panceng Kabupaten Gresik, Java East. Data collection techniques by observation and interview. The subjects of this research are owner, staff and customers of Event organizer “New Afgan Nada”. The innovation carried out by the “New Afgan Nada” event organizer service rental centers on improving service quality, providing an unforgettable experience and utilizing technology. The main supporting factors in making innovations in the rental of “New Afgan Nada” event organizer services include leadership, well-established team solidity, and an extensive network of relationships. However, on the other hand, there are some inhibiting factors, such as cost investment, fierce market competition, limited internal resources and changing opinions or ideas.